Penyelesaian Kasus Kecelakaan Lalu Lintas Yang Dilakukan Anak Dibawah Umur Di Polres Sorongberdasarkan Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak - Sitorus, Adrianus F.; Renouw, Dian Mega E.; Murary, Weron (Innovative: Journal Of Social Science Research, 2024)
Traffic accidents involving minors are  special and serious concern of the Sorong Regency government. Traffic violations committed by minors by not complying with the rules of driving on the highway cause an increase in traffic violations and traffic accidents which are also caused by parents negligence in supervising minors. The method in the research used is the descriptive method which is basic analysis to describe the general condition of the situation to facilitate the delivery of information presented in the form of tables. This research begins with a survey and data collection, in the form of primary data and secondary data. The approach method used in this research uses 3 approaches, namely: statute approach, conceptual approach, and case approach. Based on the results of the research obtained, problem solving in accident cases caused by minors using restorative justice is expected to realize a transfer of the process of resolving criminal acts out of the criminal court process and resolved through  deliberative / family process. Restorative justice is carried out through stages, namely; processing the scene of the crime, making minutes of the crime scene, conducting the investigation process, and giving time to the victim and the victim. As well as preventive efforts in reducing the level of traffic accidents are carried out by socializing or instructing to junior and senior high schools.